Overexpression of synapsin Ia in the rat calyx of Held accelerates short-term plasticity and decreases synaptic vesicle volume and active zone area - Vasileva, Mariya; Renden, Robert; Horstmann, Heinz; Gitler, Daniel; Kuner, Thomas (Frontiers in cellular neuroscience, 2013)
Synapsins are synaptic vesicle (SV) proteins organizing a component of the reserve pool of vesicles at most central nervous system synapses. Alternative splicing of the three mammalian genes results in multiple isoforms that may differentially contribute to the organization and maintenance of the SV pools. To address this, we first characterized the expression pattern of synapsin isoforms in the rat calyx of Held. At postnatal day 16, synapsins Ia, Ib, IIb and IIIa were present, while IIa - known to sustain repetitive transmission in glutamatergic terminals - was not detectable. To test if the synapsin I isoforms could mediate IIa-like effect, and if this depends on the presence of the E-domain, we overexpressed either synapsin Ia or synapsin Ib in the rat calyx of Held via recombinant adeno-associated virus-mediated gene transfer. Although the size and overall structure of the perturbed calyces remained unchanged, short-term depression and recovery from depression were accelerated upon overexpression of synapsin I isoforms. Using electron microscopic three-dimensional reconstructions we found a redistribution of SV clusters proximal to the active zones (AZ) alongside with a decrease of both AZ area and SV volume. The number of SVs at individual AZs was strongly reduced. Hence, our data indicate that the amount of synapsin Ia expressed in the calyx regulates the rate and extent of short-term synaptic plasticity by affecting vesicle recruitment to the AZ. Finally, our study reveals a novel contribution of synapsin Ia to define the surface area of AZs.